How to be minimalist about shared agency - Salomone-Sehr, J (Wiley, 2023)
What is involved in acting together with others? Most shared agency theorists endorse the Shared Intention Thesis, i.e., the claim that shared agency necessarily involves shared intentions. This article dissents from this orthodoxy and offers a minimalist account of shared agency—one where parties to shared activities need not form rich webs of interrelated psychological states. My account has two main components: a conceptual analysis of shared agency in terms of the notion of plan, and an explanation of undertheorized agency-sharing mechanisms. My analysis states that we act together just in case our activities conform to a plan and that plan figures in an explanation of our activities’ joint conformity to it. To sloganize: shared activity is plan-coordinated activity. Sometimes, plan-coordination goes by way of shared intentions. However, besides shared intentions, there are at least two additional families of agency-sharing mechanisms. The first features a central planner who determines the content of a plan and attributes the different parts of that plan to a collection of agents. The second does away with the planner and involves a roughly Darwinian selection of patterns of activity. Both families of mechanisms enable us to act together even in the absence of shared intentions.